DI-5-CUFFS: Venoconstrictive Thigh Cuffs Limit Body Fluid Changes but Not Orthostatic Intolerance Induced by a 5-Day Dry Immersion - Robin, Adrien; Auvinet, Aline; Degryse, Bernard; Murphy, Ronan; Bareille, Marie-Pierre; Beck, Arnaud; Gharib, Claude; Gauquelin-Koch, Guillemette; Daviet, Aude; Larcher, Françoise; Custaud, Marc-Antoine; Navasiolava, Nastassia (Frontiers in Physiology, 2020)
Venoconstrictive thigh cuffs are used by cosmonauts to ameliorate symptoms associated with cephalad fluid shift. A ground simulation of microgravity, using the dry immersion (DI) model, was performed to assess the effects of thigh cuffs on body fluid changes and dynamics, as well as on cardiovascular deconditioning. Eighteen healthy men (25-43yrs), randomly divided into two groups, (1) control group or (2) group with thigh cuffs worn 10h/day, underwent 5-day DI. Cardiovascular responses to orthostatic challenge were evaluated using the lower body negative pressure (LBNP) test; body fluid changes were assessed by bio-impedance and hormonal assay; plasma volume evolution was estimated using hemoglobin-hematocrit; subjective tolerance was assessed by questionnaires. DI induced a decrease in plasma volume of 15-20%. Reduction in total body water of 3-6% stabilized towards the 3rd day of DI. This reduction was derived mostly from the extracellular compartment. During the acute phase of DI, thigh cuffs limited the decrease in renin and the increase in N-terminal prohormone of brain natriuretic peptide (NT-proBNP), the loss in total body water, and tended to limit the loss in calf volume, extracellular volume and plasma volume. At the later stable phase of DI, a moderate protective effect of thigh cuffs remained evident on the body fluids. Orthostatic tolerance time dropped after DI without significant difference between groups. Thigh cuff countermeasure slowed down and limited the loss of body water and tended to limit plasma loss induced by DI. These observed physiological responses persisted during periods when thigh cuffs were removed. However, thigh cuffs did not counteract decreased tolerance to orthostatic challenge.